The evolving trajectory of conjunction use in the ELT research articles - Safari, Marzieh; Mahdavirad, Fatemeh (Frontiers in Research Metrics and Analytics, 2024)
The present study was aimed at a diachronic investigation of conjunction as a grammatical cohesive device in ELT research articles. A total number of 100 research articles concentrating on teaching writing skills in the EFL context, and were released in two extremes of 1980–82 and 2020–22 were selected. The caution was taken to choose the papers which were written by expert English writers. Working within a descriptive-analytical framework, the type and frequency of conjunctions used in the articles were examined. The results depicted that the frequency of conjunctions increased at the expense of dropping in their variation. Having looked more closely, we found that particular conjunctions grew in use while the others fell out of the writers' favor. This pattern was also visible in the studies in which non-English writers' research articles were examined. This change, therefore, is attributed to the development of the speech community and the rise of non-English writers. Eventually, we concluded that it might be better to revise our material in ESP classes to adapt to the changes in a speech community.